2014
DOI: 10.1177/0163278714553661
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Claims-Based Diagnosis of Obesity Among Medicare Beneficiaries

Abstract: Population-level data on obesity are difficult to obtain. Claims-based data sets are useful for studying public health at a population level but lack physical measurements. The objective of this study was to determine the validity of a claims-based measure of obesity compared to obesity diagnosed with clinical data as well as the validity among older adults who suffer from chronic disease. This study used data from the National Health and Nutrition Examination Survey 1999-2004 for adults aged ≥ 65 successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 13 publications
3
54
0
Order By: Relevance
“…Lloyd et al assessed the validity of obesity diagnoses recorded in Medicare claims data in 1999 to 2007 via patient‐level linkage to BMI data from the National Health and Nutrition Examination Survey (NHANES). In their cohort, the sensitivity and PPV of BMI‐related diagnoses for obesity were 18.4% and 73.6%, respectively . Consistent with our results, Lloyd et al found that individuals with more severe obesity were more likely to have a diagnosis coded in the claims data.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Lloyd et al assessed the validity of obesity diagnoses recorded in Medicare claims data in 1999 to 2007 via patient‐level linkage to BMI data from the National Health and Nutrition Examination Survey (NHANES). In their cohort, the sensitivity and PPV of BMI‐related diagnoses for obesity were 18.4% and 73.6%, respectively . Consistent with our results, Lloyd et al found that individuals with more severe obesity were more likely to have a diagnosis coded in the claims data.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, the coding of overweight/obesity and BMI is inconsistent in administrative databases. Prior studies in the USA and Canada indicate that International Classification of Diseases (ICD) diagnosis codes for obesity recorded in administrative data have a high positive predictive value (PPV; 74%‐91%) but low sensitivity (18%‐19%) . There is limited evidence from a study in women with breast cancer that the sensitivity of administrative diagnosis codes for overweight/obesity may have improved over time in the 2000s .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is impracticable to measure body weight and height for each individual in the population. Therefore, a number of studies have explored the use of diagnosis information captured in population-based administrative healthcare data for ascertaining obesity [ 7 , 8 ]. Specifically, International Classification of Diseases (ICD) codes have been used to ascertain individuals who are obese.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, International Classification of Diseases (ICD) codes have been used to ascertain individuals who are obese. Studies have demonstrated ICD-coded obesity has low sensitivity but high specificity [ 7 , 8 ]. However, there has been limited research about the predictive value of ICD-coded obesity for major chronic conditions at the population level.…”
Section: Introductionmentioning
confidence: 99%